TECHNOLOGY AND CONDITIONS OF CLASSIFIED PHYSICAL EDUCATION IN PREPARING STUDENTS FOR THE PROCESS OF PUBLIC SPORTS HEALTH (Scientific journal of the Fergana State University, 2024)
In this article, one of the main tasks of future pedagogues in modern society today is high professional competence and intellectual potential, loyalty, ideological conviction, and love for their profession. This distinguishes educators from other professions. Many programs on improving the quality and efficiency of education, forming their practical skills in subjects, and opinions on the priority tasks were expressed.